The ‘social’ in online shopping : an exploratory study of Singaporean women and the social effects of shopping on deal websites. - Poh, Aretha. (2013)
The social effects in relation to online shopping are explored through a sample of 20 Singaporean females who had previously used online shopping websites. Due to the fact that there are countless categories of online shopping websites, for the purpose of this essay, the focus is solely on deal-of-the-day websites, in particular Groupon and deal.com.sg. The aim of this research study is to examine the social effects that are brought about through the processes of shopping online. The social effects of socially constructed wellness advertisements will cause consumers to experience a state of dissonance and lead to dissatisfaction with their body image. Right from the start, the choices that are made available to consumers on deal websites originate from culturally defined standards and values of society. Bounded by limited preferences, consumers make rational choices and purchase deals that give them the best advantages and serve self-interests. The process of decision-making is accompanied with the help from word-of-mouth recommendations and social media networks. Exchange theory will be used to explain the different extents of social bonds and advantages derived from them. The results of this research study will attempt to bridge the social constraints imposed on Singaporean women and the realities of life, so that consumers can negotiate around the situation.